A comprehensive decoupling control strategy for a gas flow facility based on active disturbance rejection generalized predictive control. (4th May 2018) - Wu, Xia; Chen, Zengqiang; Zhao, Yue; Sun, Lijun; Sun, Mingwei
Abstract: A comprehensive decoupling control (CDC) method, based on the active disturbance rejection generalized predictive control (ADRC‐GPC) technology, is proposed in this paper for square multi‐input multi‐output (MIMO) systems. The central idea of this approach is that the total disturbance, which includes the partial coupling information among loops, the internal uncertainties, and the external disturbance, can be estimated by output through the extended state observer (ESO) and compensated in the feedback loop by feedback control law. Such estimating and cancelling can readily decouple the primal coupling system into multiple single‐input single output (SISO) subsystems with the form of cascade integrators. Then the generalized predictive controller is designed for each subsystem. The proposed design is effectively used in the gas flow facility. Mathematical simulations and experiments show that compared with the proportional integral derivative (PID) method, the ADRC‐GPC controller can achieve better dynamic performance, decoupling ability, disturbance rejection capability, and performance robustness.